SWOT Analysis In Education - Hayatul Fikri; Purniadi Putra (ADISAM PUBLISHER, 2022)
SWOT analysis is an analytical instrument to determine the appropriate strategy in an organization through internal (Strengths and Weaknesses) and external (Opportunities and Threats) identification to find out the real situation. This analysis can be done with two approaches, namely qualitative and quantitative approaches. There are three stages of analysis, namely the stages of data collection, data analysis and decision making.